Valoración de los servicios ecosistémicos asociados a los recursos hídricos y su escalamiento espacial sobre los disturbios ambientales en la ciudad de Alausí, Provincia de Chimborazo - Guailla Naula, Guillermo Raúl (2025)
The present research entitled “VALUATION OF ECOSYSTEM SERVICES ASSOCIATED WITH WATER RESOURCES AND THEIR SPATIAL SCALING ON ENVIRONMENTAL DISTURBANCES IN THE CITY OF ALAUSÍ, PROVINCE OF CHIMBORAZO,” aimed to analyze the importance of environmental services of provision, support, regulation and cultural, and estimate their economic value. In addition, spatial scaling was carried out to link the importance of these services with the environmental disturbances that occurred in the area, such as the landslide in 2023. The methodology used included surveys of the local population to obtain sociodemographic data and data on the perception of ecosystem services, statistical tests (Student t-test and ANOVA) to identify significant relationships, and the use of spatial scaling tools to visualize changes in the availability of water resources after the landslide. The results showed that most respondents perceive the importance of ecosystem services, particularly provisioning and cultural services. In addition, a high percentage of the population showed willingness to pay for the conservation of these services, with an average of $38.04 dollars per year. It is concluded that, although there is an appreciation for ecosystem services, it is necessary to consider the future implementation of public policies, such as payment mechanisms for environmental services that encourage the conservation of watersheds, education, and awareness programs, as well as strengthening citizen participation through the creation of community councils for water management, ensuring greater community involvement in its management.